Modelling water productivity for ecological intensification of crop sequences in the Inner Argentinean Pampas - Videla Mensegue, Horacio Rogelio (2021)
The design of crop sequences based on ecological intensification (EI) may help to restore lost agroecosystem services and to increase resource use efficiency. Our aim was to evaluate, using a modelling approach, the impact of EI-based strategies, such as changing crop sequence configuration and increasing cropping intensity and agrobiodiversity, in the Inner Argentinean Pampas (IAP) region on water productivity (WP) of crop sequences and its components, i.e. water capture (Cw) and water use efficiency (WUE). We simulated crop sequences using SWB crop model for a 50-year period in two locations of IAP region. Crop sequences, of two-year duration each, had different configurations and included sole and/or double-crops in the growing season. These crop sequences were characterized using the following indexes of EI: cropping intensity index (CII), agrobiodiversity index (ABDI), cereal proportion (CP), maize (Zea mays L.) proportion (MP) and soybean (Glycine max [L] Merrill) proportion (SP). Our main findings reveal that: i) Regardless of location, all crop sequences alternatives to those based on a high SP had a higher estimated glucose yield, ii) Estimated glucose yield, WP, Cw, and WUE were significantly related to one or more indexes of EI included in multiple lineal models, iii) The role of Cw was more important than that of WUE to increase WP, iv) The choice of crop sequence was more critical to increase Cw when decreasing rainfall, v) vapour pressure deficit appears as a meteorological variable at least as important as the total amount of rainfall and its distribution pattern to design crop sequences in the IAP. Thus, the used modelling approach allowed us to evaluate crop sequences spanning a wide range of ecological intensification indexes, which take into account the level of agrobiodiversity, cropping intensity, and the proportion of key crops in their composition, gaining useful insights to design sustainable cropping systems.